Mucosal microfolds augment mixing at the wall of the distal ileum of the brushtail possum. Issue 11 (14th August 2013) - Lentle, R. G.; Janssen, P. W. M.; DeLoubens, C.; Lim, Y. F.; Hulls, C.; Chambers, P.
Abstract: Background: Recent work suggests that mixing in the small intestine takes place in central luminal and peripheral compartments. However, while movements of villi have been described, the mechanisms by which peripheral mixing are engendered remain unclear. Methods: We examined the disposition and movement of mucosa and associated villi during contractions of the everted terminal ileum of the brushtail possum. We then simulated the effect of these movements on peripheral mixing. Key Results: Compression of the intestinal mucosa by phasic longitudinal or radial contractions created short‐lived microfolds, which were of similar scale to the attached villi. The packing density of the villous tips increased in the concavities and decreased on the crests of these microfolds. Simulations showed that these caused liquid digesta to be expelled from, or drawn into, intervillous spaces, significantly augmenting peripheral, but not bulk, luminal mixing. Conclusions & Inferences: We describe a mechanism by which peripheral mixing may be engendered by mucosal microfolds without requiring the coordinated contraction of individual villi or groups of villi. Abstract : We examined the disposition and movement of mucosa and associated villi during contractions of the everted terminal ileum of the brushtail possum and then simulated the effect of these movements on peripheral mixing. We describe a mechanism by which peripheral mixing may be engendered by mucosal microfolds without requiring the coordinated contraction of individual or groups of villi.